Concept of Wali Mujbir in Marriage (Legal Criticism of Counter Legal Draft Compilation of Islamic Law) - Musda Asmara (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
Responding to demands from a group of parties to formalize Islamic law, the Counter Legal Draft Compilation of Islamic Law (CLD KHI) team has compiled a pluralist, democratic, humanist, and gender fair Islamic law text.This manuscript reaps pros and cons during society because it is considered not in line with the values contained in the Qur’an and hadith.Because of the discrepancy between the opinions of most jurists in general with the contents of the CLD-KHI, of course, it will result in the absence of legal certainty in the future. The object of this research is only focused on the concept of walimujbir. The method used in this research is a qualitative method with a descriptive approach, data is collected openly according to what is obtained from primary and secondary sources. The results of this study indicate that the presence of a guardian in a marriage is positioned as a pillar of Marriage. In contrast, in the CLD KHI formulation, a guardian is not required in a marriage. The formulation of Islamic family law reform offered by CLD-KHI is based solely on public logic, local wisdom, and on several perspectives such as democracy, pluralism, human rights, justice, gender equality, and western ideology. In matters of marriage, especially regarding guardians of mujbir, the ideas of CLD-KHI are different and even contradict the common understanding of principles of Islamic teachings and practices.